Open Repair of the Triangular Fibrocartilage Complex from Palmar Aspect - Moritomo, Hisao (Journal of Wrist Surgery, 2015)
Background Although foveal tears of the triangular fibrocartilage complex (TFCC) can be surgically reattached to the fovea via a dorsal approach, the foveal lesion is difficult to visualize from the dorsal side because the extensor carpi ulnaris (ECU) sheath floor and the superficial dorsal limb of the radioulnar ligament hinders the view of the fovea.Materials and Methods Twenty-one patients with foveal tears were treated by an open repair method from the palmar aspect. Pain, instability, motion, and grip strength were evaluated after a mean follow-up period of 26 months, and each patient was rated according to the Mayo Modified Wrist Score (MMWS).Description of Technique A 4-cm skin incision is made on the palmar aspect of the ulnar fovea. The ulnar fovea is exposed through a transverse capsulotomy of the distal radioulnar joint. The distal aspect of the TFCC is also exposed between the ECU tendon sheath and the ulnotriquetral ligament. After curettage of the scar tissue in the fovea, the deep palmar and dorsal limbs of the TFCC are sutured back to the fovea using a suture anchor technique.Results Foveal TFCC tears could be repaired via a palmar surgical approach without violating the floor of the ECU tendon sheath and the superficial dorsal limb. Excellent results were achieved in 18 patients, and a good result was achieved in three.Conclusions Our result compared favorably with those reported for dorsal approach. The palmar surgical approach facilitates the inspection and repair of the TFCC foveal tears.Level of Evidence IV
Keywords: DRUJ instability; TFCC foveal tear; open repair; CT arthrography; surgical approach